Description of three new species of the genus Mata Distant, 1906 (Hemiptera: Cicadidae: Cicadinae: Oncotympanini) with notes on their natural history from Indian state of Meghalaya, India - Sarkar, Vivek; Mahapatra, Cuckoo; Mohapatra, Pratyush P.; Nair, Manoj V.; Kunte, Krushnamegh (Zootaxa, 2021)
Three new species of the Asian genus Mata Distant, 1906 (Hemiptera: Cicadidae) viz. Mata lenonia sp.nov.; Mata ruffordii sp.nov. and Mata meghalayana sp.nov. are described from Indian state of Meghalaya. Keys and taxonomic descriptions of these species are provided with detailed accounts of their natural history and acoustics.